Fungsi dan Makna Desain Karakter Wayang Potehi Lakon Shi Jhin Kwie - Patriantoro, Teguh Hartono (LP2M ISBI Bandung, 2020)
The object of this research is to analyze the functions and meanings of the characters of Wayang Potehi or Potehi puppet by taking the play of Shi Jin Kwie. The play is a popular fiction story which was later adapted into the story of Prabu Lisanpuro in Javanese theater (ketoprak). The results of the research found the organology structure of Wayang Potehi. It consists of 2, namely (1) parts of the body; head, hand, feet, and (2) clothing; along with ornaments and additional accessories such as swords and hats. The head section can be identified as the interpretation of the puppet character. For instance, an antagonist character depicted as if he was using a Balinese leak mask with his mouth open and angry. The clothes could be the interpretation of social status. For example, the villagers wear plain clothes without ornaments, while the nobles use yellow, red clothing with a dragon/ phoenix pattern. There are 4 types of character design in this show, specifically (1) the firm/ wise character, (2) the entertaining character, (3) the functionaries/ officials/ priyayi character, (4) the antagonist character. Especially for entertaining characters, it has a dual function; to return the underlying causes of the story and become the spy of the enemy. The methods used in this research are personality theory and functional theory approaches. Keywords: potehi character design, Shi Jin Kwie, Function of potehi